2021
DOI: 10.22374/ijmsch.v4i1.52
|View full text |Cite
|
Sign up to set email alerts
|

The Making of Men Program: A Mixed-Methods Evaluation of a Gender-Sensitive Rite of Passage Program for Adolescent Males

Abstract: IntroductionCurrent gendered health disparities impacting the wellbeing of boys and young men require new early intervention-focussed approaches. Health promotion programs developed with young men’s health needs and preferences in mind commonly report positive outcomes. Male-specific rite of passage programs aim to formally acknowledge the life-stage transition from boyhood to manhood through a holistic focus on identity, community, and social responsibility. While these programs are growing in popularity, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Furthermore, temporal associations were identified across all outcomes, with effects strongest for weekly users. 59 The findings were not reported by participants' Indigenous status.…”
Section: Alcohol Consumptionmentioning
confidence: 91%
See 4 more Smart Citations
“…Furthermore, temporal associations were identified across all outcomes, with effects strongest for weekly users. 59 The findings were not reported by participants' Indigenous status.…”
Section: Alcohol Consumptionmentioning
confidence: 91%
“…Silins et al 59 identified significant associations between increasing frequency of alcohol use and lower educational attainment, through the integration of data from three longitudinal studies from Australia and New Zealand. 59 These findings showed 1.33-2.03 times higher odds of high school noncompletion, university nonenrollment, and degree nonattainment for weekly drinkers compared with those who had never used alcohol. Furthermore, temporal associations were identified across all outcomes, with effects strongest for weekly users.…”
Section: Alcohol Consumptionmentioning
confidence: 99%
See 3 more Smart Citations